An Inverse Problem of Temperature Optimization in Hyperthermia by Controlling the Overall Heat Transfer Coefficient - Seyed Ali Aghayan; Dariush Sardari; Seyed Rabii Mahdi Mahdavi; Mohammad Hasan Zahmatkesh (Journal of Applied Mathematics)
A novel scheme to obtain the optimum tissue heating condition during hyperthermia treatment is proposed. To do this, the effect of the controllable overall heat transfer coefficient of the cooling system is investigated. An inverse problem by a conjugated gradient with adjoint equation is used in our model. We apply the finite difference time domain method to numerically solve the tissue temperature distribution using Pennes bioheat transfer equation. In order to provide a quantitative measurement of errors, convergence history of the method and root mean square of errors are also calculated. The effects of heat convection coefficient of water and thermal conductivity of casing layer on the control parameter are also discussed separately.